Biographical research methods - Eichsteller, Marta; Davis, Howard H. (SAGE Publications, 2022)
Biographical data provide unique insights into social life, but they also pose some significant challenges for social science researchers. This book offers a systematic, flexible guide to using biographical narrative methods in your research project. Drawing upon the authors' own research, as well as case studies from a range of international contexts and disciplines, the book illustrates how biographical approaches can be tailored to different research questions and environments. This book will help you to: · Navigate any complexities or missteps when undertaking real-world research · Apply your analytical and research tools to your research question · Choose the right research design for your project, whether single or mixed methods · Ground your understanding within diverse real-world research examples. Clear, adaptable, and applied, this is your definitive guide to working with biographical methods"